2007
DOI: 10.1590/s0004-27302007000200018
|View full text |Cite
|
Sign up to set email alerts
|

Silent myocardial ischemia screening in patients with diabetes mellitus

Abstract: The prevalence of diabetes mellitus is fairly increasing, especially in the developing countries. Diabetes is a major cardiovascular risk factor; it often leads to severe cardiovascular complications, and coronary artery disease (CAD) is the main cause of death in diabetic patients. Silent myocardial ischemia (SMI) is more frequent in diabetic patients. The progress made in detection and treatment of CAD allows reconsidering the screening of SMI, in the hope that early CAD diagnosis leads to a more effective t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 47 publications
(26 reference statements)
0
18
0
4
Order By: Relevance
“…For patient with inconclusive ECG stress test, myocardial scintigraphy seems more accurate than stress echocardiography. Coronary angiogram should be performed in case of positive stress test (31) . The second phase of the DIAD study (n = 1123) already showed that screening with MPS all asymptomatic diabetic patients is not cost-effective (32) .…”
Section: Discussionmentioning
confidence: 99%
“…For patient with inconclusive ECG stress test, myocardial scintigraphy seems more accurate than stress echocardiography. Coronary angiogram should be performed in case of positive stress test (31) . The second phase of the DIAD study (n = 1123) already showed that screening with MPS all asymptomatic diabetic patients is not cost-effective (32) .…”
Section: Discussionmentioning
confidence: 99%
“…Estudios anteriores reportan una prevalencia de isquemia miocárdica silente en el diabético entre 9% y 57% [3][4][5][14][15][16][17] . En la muestra estudiada se encontró 26,5% de isquemia miocárdica silente por resultados del gated-SPECT y 25,5% según coronariografía.…”
Section: Discusión Según American College Of Cardiology Y Americanunclassified
“…Le choix initial est guidé par l'atteinte viscérale : bêta-bloquants ou inhibiteurs de l'enzyme de conversion (IEC) en cas d'antécédent d'infarctus, IEC ou antagonistes des récep-teurs de l'angiotensine-II (ARA-II) en cas de néphropathie, diurétiques, bêta-bloquants, IEC (ou ARA-II si intolérance), anti-aldostérone si insuffisance cardiaque, bêta-bloquants ou inhibiteurs calciques de longue durée d'action en cas d'atteinte coronaire [4] L'échocardiographie ou la scintigraphie myocardique de stress ne sont indiquées que lorsque l'épreuve d'effort est faiblement positive, litigieuse (sous maximale), ou ininterprétable [WolffParkinson-White (WPW), bloc de branche gauche (BBG), pacemaker]. Les valeurs prédictives positives de ces 2 techniques sont comparables pour le diagnostic de sténose coronaire, de même que leurs valeurs prédictives négatives dans la survenue d'événement cardiovasculaire [8,9]. La coronarographie conventionnelle est indiquée chez les patients avec épreuve d'effort très positive, territoire ischémique > 10 % à l'imagerie non invasive, ou anomalies ischémiques de l'ECG de repos (ondes Q de nécrose, ischémie sous épicardique sans hypertrophie ventriculaire gauche (HVG) [7].…”
Section: Bénéfices D'une Prise En Charge Globaleunclassified